GABAB receptor subtypes differentially modulate synaptic inhibition in the dentate gyrus to enhance granule cell output. (25th March 2013) - Foster, Joshua D; Kitchen, Ian; Bettler, Bernhard; Chen, Ying
<x xml:space="preserve">Abstract</x> Background and Purpose Activation of GABAB receptors in the dentate gyrus (DG) enhances granule cell (GC) activity by reducing synaptic inhibition imposed by hilar interneurons. This disinhibitory action facilitates signal transfer from the perforant path to the hippocampus. However, as the two main molecular subtypes, GABAB(1a, 2) and GABAB(1b, 2) receptors, prefer axonal terminal and dendritic compartments, respectively, they may modulate the hilar pathways at different synaptic localizations. We examined their relative expression and functions in the DG. Experimental Approach The localization of GABAB subtypes was revealed immunohistochemically using subunit‐selective antibodies in GABAB1a–/– and GABAB1b–/– mice. Effects of subtype activation by the GABAB receptor agonist, baclofen, were examined on the perforant path‐stimulated GC population activities in brain slices. Key Results GABAB(1a, 2) receptors were concentrated in the inner molecular layer, the neuropil of the hilus and hilar neurons at the border zone; while GABAB(1b, 2) receptors dominated the outer molecular layer and hilar neurons in the deep layer, showing their differential localization on GC dendrite and in the hilus. Baclofen enhanced the GC population spike to a larger extent in the GABAB1b–/– mice, demonstrating exclusively disinhibitory roles of the GABAB(1a, 2) receptors. Conversely, in the GABAB1a–/– mice baclofen not only enhanced but also inhibited the population spike during GABAA blockade, revealing both disinhibitory and inhibitory effects of GABAB(1b, 2) receptors. Conclusions and Implications The GABAB(1a, 2) and GABAB(1b, 2) receptor subtypes differentially modulate GC outputs via selective axonal terminal and dendritic locations in the hilar pathways. The GABAB(1a, 2) receptors exclusively mediate disinhibition, thereby playing a greater role in gating signal transfer for hippocampal spatial and pattern learning.